The Role of Zeolite (Microporous Crystalline Aluminosilicates) In Catalytic Pyrolysis of Waste High- and Low-Density Polyethylene Bags for Production of Fuel and Chemicals: A Review - Jibreel, Umar Muhammad; Bayero, Amina Salihi; Mohamaed, Musa Ibrahim; Muzakkari, Bashir Audu (Universitas Islam Indonesia, 2024)
This review provides a state-of-the-art summary of the role which zeolite plays as a catalyst via pyrolysis as a way of recovering fuels and chemicals from waste high and or low density polyethylene bags. It also highlighted the two types of zeolite (natural or synthetic) which are used as a two-stage pyrolysis−catalysis in giving a free waxing product to pure fuel and chemicals which can be subjected to further analyzing and or upgrading. As yield of oil/wax decreased with the addition of a zeolite as catalyst from 44 and 51 wt.%, (depending on the waste high density polyethylene “HDPE” or low density polyethylene bags “LDPE” and other factors). However, the composition of the pyrolysis−catalysis oils significantly increased in aromatic hydrocarbon content accordingly. In addition, the composition of the oils shifted from high molecular weight hydrocarbons (C16+) to fuel range hydrocarbons (C5−C15), with a high content of single-ring aromatic hydrocarbons such as benzene, toluene, ethylbenzene, xylenes, and styrene. This process shows great potential for production of fuels or chemicals, and also addresses the urgent issue of waste HDPE and or LDPE disposal.